Evaluation of Psoriasis Area and Severity Index as a Proxy for Biomarkers of Systemic Disease under Treatment with Tumour Necrosis Factor-alpha and Interleukin 12/23 Antagonists in Patients with Psoriasis: A Retrospective Cohort Study of 186 Treatment Cycles - Jochen H.O. Hoffmann; Christian Knoop; Knut Schäkel; Alexander H. Enk; Eva N. Hadaschik (Medical Journals Sweden, 2021)
The efficacy of psoriasis treatments is usually evaluated using the Psoriasis Area and Severity Index (PASI). However, there is a lack of systematic statistical assessments of PASI as a proxy for systemic disease in individual patients. Therefore, a retrospective study of 186 treatments with adalimumab, etanercept, and ustekinumab for psoriasis (341 patient-years) was performed. While PASI significantly and independently correlated with biomarkers of systemic inflammation (especially neutrophil-to-lymphocyte ratio, C-reactive protein), the strengths were only weak-to-moderate and varied considerably inter-individually. A decrease in PASI indicated a neutrophil-to-lymphocyte ratio decrease and a C-reactive protein decrease or stable low margin C-reactive protein in ≥ 80%. Sensitivity, specificity, and positive predictive value of PASI 0 and PASI 2.75 (optimal Youden Index) for low cardiovascular risk C-reactive protein were 24%, 92%, 85%, and 62%, 61%, 76%, respectively. Performance was similar using absolute thresholds and PASI 100 or PASI 75, and overall worse for low cardiovascular risk neutrophil-to-lymphocyte ratio and if psoriasis arthritis was present. In conclusion, PASI allows robust low-order estimates of systemic inflammation, but cannot substitute for laboratory biomarkers for more precise assessments.